2005
DOI: 10.1007/s00705-005-0614-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cis-acting elements in the rubella virus subgenomic RNA that play a role in its translation

Abstract: The subgenomic (SG) mRNA of rubella virus (RUB) contains the structural protein open reading frame (SP-ORF) that is translated to produce the three virion structural proteins: capsid (C) and glycoproteins E2 and E1. RUB expression vectors have been developed that express heterologous genes from the SG RNA, including replicons which replace the SP-ORF with a heterologous gene, and these expression vectors are candidate vaccine vectors. In the related alphaviruses, translational enhancing elements have been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Since RUB replication occurs in the cytoplasm, localization of C⌬8 to the nucleus would prevent it from acting directly on any step in the replication cycle, explaining its inability to rescue the replication of mutant replicons. We recently discovered that the C protein contains a stretch of four arginines (residues 60 to 63) that act as a nuclear localization signal when only the amino-terminal half (residues 1 to 151) of the protein is expressed (21). That the C⌬8 protein (residues 9 to 277) also localizes to the nucleus indicates that the eight N-terminal amino acids and residues in the C-terminal half of the protein are necessary to override the ability of stretches of basic amino acids in the C protein sequence, which are putatively present to interact with electronegative RNA in the capsid, to serve as nuclear localization signals.…”
Section: Discussionmentioning
confidence: 99%
“…Since RUB replication occurs in the cytoplasm, localization of C⌬8 to the nucleus would prevent it from acting directly on any step in the replication cycle, explaining its inability to rescue the replication of mutant replicons. We recently discovered that the C protein contains a stretch of four arginines (residues 60 to 63) that act as a nuclear localization signal when only the amino-terminal half (residues 1 to 151) of the protein is expressed (21). That the C⌬8 protein (residues 9 to 277) also localizes to the nucleus indicates that the eight N-terminal amino acids and residues in the C-terminal half of the protein are necessary to override the ability of stretches of basic amino acids in the C protein sequence, which are putatively present to interact with electronegative RNA in the capsid, to serve as nuclear localization signals.…”
Section: Discussionmentioning
confidence: 99%
“…RNA secondary structures often play important roles in viral replication, viral subgenomic RNA synthesis, and translation efficiency (14,20). Therefore, to further understand how mutations in the junction region may affect virus infectivity, we performed RNA secondary structure prediction by using the program RNA FOLD (http:// www.bioinfo.rpi.edu/ϳzukerm/rna/) for the junction regions of the wild-type swine HEV, mutant-1, mutant-3, and mutant-5, all of which were successfully recovered in pigs but with different efficiencies.…”
Section: Construction Of Hev Mutants and Determination Of Their Levelmentioning
confidence: 99%
“…We subsequently demonstrated that swine HEV can cross species barriers and infect nonhuman primates (16) and that pig handlers in the United States and other countries are at increased risk of zoonotic HEV infection (18). All swine HEV isolates thus far identified from pigs belong to either genotype 3 or genotype 4 and in many cases are genetically indistinguishable from human HEV genotypes 3 and 4 (19,20,31). Swine HEV infection in specific-pathogenfree pigs provided us a unique animal model to study HEV replication and pathogenesis (6,10).…”
mentioning
confidence: 99%
“…It is known that P200 possesses protease activity that cleaves at residue 1301 (out of 2,116 residues) to produce the two mature replicase proteins P150 and P90 (9, 24). P150 and P90 form a complex that synthesizes two positive-strand RNAs, genomic and subgenomic RNA (9, 22, 24), but it is not clear if this interaction takes place in the context of P200.A subgenomic RNA that is identical to the 3= terminal third of the genomic RNA is produced during RUBV RNA synthesis (3,34,44,46), and this second ORF encodes the structural proteins N-CP-E2-E1-C. While serving as an mRNA for the structural proteins appears to be the only role of the subgenomic RNA, newly synthesized genomic RNAs subsequently either undergo translation, producing P200 to recapitulate RC assembly and RNA synthesis, or are packaged into virus particles.…”
mentioning
confidence: 99%
“…A subgenomic RNA that is identical to the 3= terminal third of the genomic RNA is produced during RUBV RNA synthesis (3,34,44,46), and this second ORF encodes the structural proteins N-CP-E2-E1-C. While serving as an mRNA for the structural proteins appears to be the only role of the subgenomic RNA, newly synthesized genomic RNAs subsequently either undergo translation, producing P200 to recapitulate RC assembly and RNA synthesis, or are packaged into virus particles.…”
mentioning
confidence: 99%